Diamond saw blade and method for manufacturing the same

By using diamond saw blades as the matrix material, combining silicon carbide, cerium powder, nickel powder, copper powder and other raw materials, and processing the modified additives and coordinated treatment agents, the impact toughness of diamond saw blades is solved. The lack of wear resistance and thermal conductivity has significantly improved its resistance to salt spray, water, moisture, hot and cold stability, and improved the efficiency of the product.

CN119216582BActive Publication Date: 2025-02-18NANAN MINGJI DIAMOND TOOL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411749864.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-02-18
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

Existing diamond saw blades have poor performance in impact toughness, wear resistance and thermal conductivity, and their resistance to salt spray, water, wetness, hot and cold stability is also poor, limiting their use efficiency.

Method used

Diamond powder is used as the matrix material, silicon carbide, cerium powder, nickel powder, copper powder, modification additives and coordination treatment agents are added to enhance the performance and effect of the system through the harmony between the raw materials. Specific processes include preparation of impregnating agents, ultrasonic impregnation treatment, ball mill improvement treatment, etc., to form efficient modification additives and coordinated treatment agents.

Benefits of technology

The coordinated improvement of the impact toughness, wear resistance and thermal conductivity of diamond saw blades is achieved, and its resistance to salt spray, water, moisture, hot and cold stability is significantly improved, and the use efficiency of the product is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention relates to the technical field of diamond saw blades, and in particular to a diamond saw blade and a manufacturing method thereof. The diamond saw blade comprises a main matrix, on which a diamond bit is arranged, and the diamond bit is used for sawing a workpiece; the diamond bit comprises the following raw materials by weight: 35-40 parts of diamond powder, 10-15 parts of silicon carbide, 9-13 parts of modified additives, 2-5 parts of cerium powder, 2-5 parts of nickel powder, 2-5 parts of copper powder, and 8-12 parts of a coordination treatment agent. The diamond saw blade of the present invention adopts a main matrix to match a diamond bit, and the diamond bit adopts diamond powder as a matrix material, and silicon carbide, cerium powder, nickel powder and copper powder are added, and modified additives and coordination treatment agents are also added. Through the coordination and mutual assistance between the raw materials, the performance effect of the system is enhanced, and the product realizes coordinated improvement of impact toughness, wear resistance and thermal conductivity, and the product has remarkable effects on salt spray water resistance and cold and heat stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of diamond saw blades, and in particular to a diamond saw blade and a manufacturing method thereof. Background Art

[0002] Diamond saw blade is a cutting tool, widely used in the processing of hard and brittle materials such as concrete, refractory materials, stone, ceramics, etc. Diamond saw blade is mainly composed of two parts: the base and the cutter head. The base is the main supporting part of the bonded cutter head.

[0003] Existing diamond saw blades have poor impact toughness performance and low wear resistance. It is difficult to achieve coordinated improvement in impact toughness, wear resistance and thermal conductivity. In addition, the products have poor resistance to salt spray, water humidity and cold and heat stability, which limits the use efficiency of the products. Summary of the invention

[0004] In view of the defects of the prior art, the object of the present invention is to provide a diamond saw blade and a method for manufacturing the same, so as to solve the problems raised in the above background technology.

[0005] The present invention solves the technical problem by adopting the following technical solution:

[0006] The present invention provides a diamond saw blade, which comprises a main substrate, on which a diamond bit is arranged, and the diamond bit is used for sawing a workpiece;

[0007] The diamond segment comprises the following raw materials in parts by weight:

[0008] 35-40 parts of diamond powder, 10-15 parts of silicon carbide, 9-13 parts of modifying additives, 2-5 parts of cerium powder, 2-5 parts of nickel powder, 2-5 parts of copper powder, and 8-12 parts of coordination treatment agent.

[0009] Preferably, the mesh size of the diamond powder and silicon carbide is 800 mesh; the mesh size of the cerium powder, nickel powder and copper powder is 400 mesh.

[0010] Preferably, the preparation method of the modified additive is:

[0011] S01: Preparation of impregnating agent:

[0012] 3-5 parts of mullite powder and 2-4 parts of zirconium silicate are mixed in 10-15 parts of potassium permanganate solution by weight, and then washed, filtered and dried to obtain composite powder;

[0013] 4-6 parts of composite powder, 2-4 parts of silane coupling agent KH550 and 1-3 parts of stearic acid are mixed by weight and added into 8-12 parts of sodium alginate solution and stirred sufficiently to obtain an impregnating agent;

[0014] S02: first immersing the kaolin in an impregnating agent of 3-5 times the total weight of the kaolin for ultrasonic impregnation treatment, and obtaining a kaolin impregnation solution after the impregnation is completed;

[0015] S03: The kaolin impregnation liquid and the modifying agent are mixed in a weight ratio of 3:5 and ball-milled at a speed of 1500 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water, filtered and dried to obtain the modified additive.

[0016] The modified additive is based on kaolin, is treated by ultrasonic impregnation with an impregnating agent, and then is improved by ball milling with a modified adjusting agent. The impregnating agent is improved by activation of mullite powder and zirconium silicate with a potassium permanganate solution, and then is blended with an alkane coupling agent KH550, stearic acid, and a sodium alginate solution, so that the obtained impregnating agent can better reinforce the mullite powder and zirconium silicate into the kaolin system, and optimize the performance effect of the system. The carbon fiber and calcite powder in the modified adjusting agent are improved by blending with a lanthanum chloride solution and a dopamine hydrochloride solution, and the obtained modified lanthanum liquid can be better blended with flaky nano alumina. The flaky structure of the flaky nano alumina and the fiber structure of the carbon fiber are used, and the calcite powder is blended, and then the modified additive is processed by the specific process of the invention, so that the obtained modified additive reinforces the performance effect of the system in the system, thereby further improving the product performance.

[0017] Preferably, the mass fraction of the potassium permanganate solution is 2-5%; the mass fraction of the sodium alginate solution is 3-5%.

[0018] Preferably, the ultrasonic power of the ultrasonic immersion treatment is 350-400W, and the ultrasonic time is 30-40min.

[0019] Preferably, the preparation method of the adjusting agent is:

[0020] Add 1-3 parts of carbon fiber and 2-4 parts of calcite powder to 5-7 parts of lanthanum chloride solution by weight, stir and mix, then add 2-4 parts of dopamine hydrochloride solution and continue to mix thoroughly to obtain a modified lanthanum solution;

[0021] The flaky nano-alumina and the modified lanthanum liquid are stirred and modified in a weight ratio of 3:5. After the stirring is completed, the mixture is filtered and dried to obtain a modified agent.

[0022] Preferably, the mass fraction of the lanthanum chloride solution is 3-5%; the mass fraction of the dopamine hydrochloride solution is 2-4%.

[0023] Preferably, the stirring speed of the stirring modification treatment is 550-750 r / min, and the stirring time is 35-45 min.

[0024] Preferably, the specific preparation method of the coordination treatment agent is:

[0025] S101: immersing boron nitride in a sufficient amount of 2-5% by weight sodium dodecylbenzene sulfonate solution and stirring sufficiently to obtain a boron nitride liquid; then adding 3-5 parts by weight of nano silica sol and 1-3 parts by weight of yttrium oxide to 5-8 parts of the boron nitride liquid and mixing sufficiently to obtain a sol regulator;

[0026] S102: Add 2-4 parts of sodium carboxymethyl cellulose to 5-8 parts of sodium silicate solution by weight, then add 2-4 parts of sol regulator and stir thoroughly, then filter and dry to obtain a coordination treatment agent.

[0027] The boron nitride in the coordination treatment agent is treated with sodium dodecylbenzene sulfonate solution, so that it can better blend nano-silica sol and yttrium oxide, and then through the co-formulation of sodium carboxymethyl cellulose and sodium silicate solution, the coordination treatment agent system formed is based on boron nitride and doped with the rare earth property of yttrium, which can better reinforce and coordinate the coordination treatment agent with the modified additive, thereby further improving the performance of the product.

[0028] Preferably, the mass fraction of the sodium silicate solution is 3-5%.

[0029] The present invention also provides a method for preparing a diamond saw blade, comprising the following steps:

[0030] First, diamond powder, silicon carbide, modified additives, cerium powder, nickel powder, copper powder and coordination treatment agent are mixed thoroughly, and then molded in a mold with a molding pressure of 20MPa and a molding time of 1h. After the molding is completed, demolding is performed and then sintered at 820-850℃ for 1h to obtain a diamond segment. Finally, the diamond segment and the main substrate are welded together to obtain a diamond saw blade.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] The diamond saw blade of the present invention adopts a main matrix to cooperate with a diamond cutter head, and the diamond cutter head adopts diamond powder as a matrix material, and silicon carbide, cerium powder, nickel powder and copper powder are added, and a modifying additive and a coordinating treatment agent are added. Through the coordination and mutual assistance between the raw materials, the performance effect of the system is enhanced, and the product achieves coordinated improvement in impact toughness, wear resistance and thermal conductivity, and the product has remarkable effects on salt spray and water resistance and cold and heat stability. DETAILED DESCRIPTION

[0033] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] A diamond saw blade of this embodiment includes a main substrate, on which a diamond bit is arranged, and the diamond bit is used for sawing a workpiece;

[0035] The diamond segment comprises the following raw materials in parts by weight:

[0036] 35-40 parts of diamond powder, 10-15 parts of silicon carbide, 9-13 parts of modifying additives, 2-5 parts of cerium powder, 2-5 parts of nickel powder, 2-5 parts of copper powder, and 8-12 parts of coordination treatment agent.

[0037] The mesh size of the diamond powder and silicon carbide in this embodiment is 800 mesh; the mesh size of the cerium powder, nickel powder and copper powder is 400 mesh.

[0038] The preparation method of the modified additive of this embodiment is:

[0039] S01: Preparation of impregnating agent:

[0040] 3-5 parts of mullite powder and 2-4 parts of zirconium silicate are mixed in 10-15 parts of potassium permanganate solution by weight, and then washed, filtered and dried to obtain composite powder;

[0041] 4-6 parts of composite powder, 2-4 parts of silane coupling agent KH550 and 1-3 parts of stearic acid are mixed by weight and added into 8-12 parts of sodium alginate solution and stirred sufficiently to obtain an impregnating agent;

[0042] S02: first immersing the kaolin in an impregnating agent of 3-5 times the total weight of the kaolin for ultrasonic impregnation treatment, and obtaining a kaolin impregnation solution after the impregnation is completed;

[0043] S03: The kaolin impregnation liquid and the modifying agent are mixed in a weight ratio of 3:5 and ball-milled at a speed of 1500 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water, filtered and dried to obtain the modified additive.

[0044] The mass fraction of the potassium permanganate solution in this embodiment is 2-5%; the mass fraction of the sodium alginate solution is 3-5%; the ultrasonic power of the ultrasonic immersion treatment is 350-400W, and the ultrasonic time is 30-40min.

[0045] The preparation method of the modified agent of this embodiment is:

[0046] Add 1-3 parts of carbon fiber and 2-4 parts of calcite powder to 5-7 parts of lanthanum chloride solution by weight, stir and mix, then add 2-4 parts of dopamine hydrochloride solution and continue to mix thoroughly to obtain a modified lanthanum solution;

[0047] The flaky nano-alumina and the modified lanthanum liquid are stirred and modified in a weight ratio of 3:5. After the stirring is completed, the mixture is filtered and dried to obtain a modified agent.

[0048] The mass fraction of the lanthanum chloride solution in this embodiment is 3-5%; the mass fraction of the dopamine hydrochloride solution is 2-4%.

[0049] The stirring speed of the stirring modification treatment in this embodiment is 550-750 r / min, and the stirring time is 35-45 min.

[0050] The specific preparation method of the coordination treatment agent of this embodiment is:

[0051] S101: immersing boron nitride in a sufficient amount of 2-5% by weight sodium dodecylbenzene sulfonate solution and stirring sufficiently to obtain a boron nitride liquid; then adding 3-5 parts by weight of nano silica sol and 1-3 parts by weight of yttrium oxide to 5-8 parts of the boron nitride liquid and mixing sufficiently to obtain a sol regulator;

[0052] S102: Add 2-4 parts of sodium carboxymethyl cellulose to 5-8 parts of sodium silicate solution by weight, then add 2-4 parts of sol regulator and stir thoroughly, then filter and dry to obtain a coordination treatment agent.

[0053] The mass fraction of the sodium silicate solution in this embodiment is 3-5%.

[0054] A method for preparing a diamond saw blade in this embodiment comprises the following steps:

[0055] First, diamond powder, silicon carbide, modified additives, cerium powder, nickel powder, copper powder and coordination treatment agent are mixed thoroughly, and then molded in a mold with a molding pressure of 20MPa and a molding time of 1h. After the molding is completed, demolding is performed and then sintered at 820-850℃ for 1h to obtain a diamond segment. Finally, the diamond segment and the main substrate are welded together to obtain a diamond saw blade.

[0056] Embodiment 1: A diamond saw blade, comprising a main substrate, on which a diamond bit is arranged, and the diamond bit is used for sawing a workpiece;

[0057] The diamond segment comprises the following raw materials in parts by weight:

[0058] 35 parts of diamond powder, 10 parts of silicon carbide, 9 parts of modifying additives, 2 parts of cerium powder, 2 parts of nickel powder, 2 parts of copper powder, and 8 parts of coordination treatment agent.

[0059] The mesh size of the diamond powder and silicon carbide in this embodiment is 800 mesh; the mesh size of the cerium powder, nickel powder and copper powder is 400 mesh.

[0060] The preparation method of the modified additive of this embodiment is:

[0061] S01: Preparation of impregnating agent:

[0062] 3 parts of mullite powder and 2 parts of zirconium silicate are mixed in 10 parts of potassium permanganate solution by weight, and then washed, filtered and dried to obtain composite powder;

[0063] 4 parts of composite powder, 2 parts of silane coupling agent KH550 and 1 part of stearic acid were mixed by weight and added into 8 parts of sodium alginate solution and stirred thoroughly to obtain an impregnating agent;

[0064] S02: first immersing the kaolin in an impregnating agent of 3 times the total weight of the kaolin for ultrasonic impregnation treatment, and obtaining a kaolin impregnation solution after the impregnation is completed;

[0065] S03: The kaolin impregnation liquid and the modifying agent are mixed in a weight ratio of 3:5 and ball-milled at a speed of 1500 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water, filtered and dried to obtain the modified additive.

[0066] The mass fraction of the potassium permanganate solution in this embodiment is 2%; the mass fraction of the sodium alginate solution is 3%; the ultrasonic power of the ultrasonic immersion treatment is 350W, and the ultrasonic time is 30 minutes.

[0067] The preparation method of the modified agent of this embodiment is:

[0068] Add 1 part of carbon fiber and 2 parts of calcite powder to 5 parts of lanthanum chloride solution by weight, stir and mix, then add 2 parts of dopamine hydrochloride solution and continue to mix thoroughly to obtain a modified lanthanum solution;

[0069] The flaky nano-alumina and the modified lanthanum liquid are stirred and modified in a weight ratio of 3:5. After the stirring is completed, the mixture is filtered and dried to obtain a modified agent.

[0070] The mass fraction of the lanthanum chloride solution in this embodiment is 3%; the mass fraction of the dopamine hydrochloride solution is 2%.

[0071] The stirring speed of the stirring modification treatment in this embodiment is 550 r / min, and the stirring time is 35 min.

[0072] The specific preparation method of the coordination treatment agent of this embodiment is:

[0073] S101: immersing boron nitride in a sufficient amount of 2% by weight sodium dodecylbenzene sulfonate solution and stirring sufficiently to obtain a boron nitride liquid; then adding 3 parts of nano-silica sol and 1 part of yttrium oxide by weight to 5 parts of the boron nitride liquid and mixing sufficiently to obtain a sol regulator;

[0074] S102: Add 2 parts of sodium carboxymethyl cellulose to 5 parts of sodium silicate solution by weight, then add 2 parts of sol regulator and stir thoroughly, then filter and dry to obtain a coordination treatment agent.

[0075] The mass fraction of the sodium silicate solution in this embodiment is 3%.

[0076] A method for preparing a diamond saw blade in this embodiment comprises the following steps:

[0077] First, diamond powder, silicon carbide, modified additives, cerium powder, nickel powder, copper powder and coordination treatment agent are mixed thoroughly, and then molded in a mold with a molding pressure of 20MPa and a molding time of 1h. After the molding is completed, demolding is performed and then sintering is performed at 820°C for 1h to obtain a diamond segment. Finally, the diamond segment and the main substrate are welded together to obtain a diamond saw blade.

[0078] Embodiment 2: A diamond saw blade, comprising a main substrate, on which a diamond bit is arranged, and the diamond bit is used for sawing a workpiece;

[0079] The diamond segment comprises the following raw materials in parts by weight:

[0080] 40 parts of diamond powder, 15 parts of silicon carbide, 13 parts of modifying additives, 5 parts of cerium powder, 5 parts of nickel powder, 5 parts of copper powder, and 12 parts of coordination treatment agent.

[0081] The mesh size of the diamond powder and silicon carbide in this embodiment is 800 mesh; the mesh size of the cerium powder, nickel powder and copper powder is 400 mesh.

[0082] The preparation method of the modified additive of this embodiment is:

[0083] S01: Preparation of impregnating agent:

[0084] 5 parts of mullite powder and 4 parts of zirconium silicate are mixed in 15 parts of potassium permanganate solution by weight, and then washed, filtered and dried to obtain composite powder;

[0085] 6 parts of composite powder, 4 parts of silane coupling agent KH550 and 3 parts of stearic acid were mixed by weight and added into 12 parts of sodium alginate solution and stirred thoroughly to obtain an impregnating agent;

[0086] S02: first immersing the kaolin in an impregnating agent of 5 times the total weight of the kaolin for ultrasonic impregnation treatment, and obtaining a kaolin impregnation solution after the impregnation is completed;

[0087] S03: The kaolin impregnation liquid and the modifying agent are mixed in a weight ratio of 3:5 and ball-milled at a speed of 1500 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water, filtered and dried to obtain the modified additive.

[0088] The mass fraction of the potassium permanganate solution in this embodiment is 5%; the mass fraction of the sodium alginate solution is 5%; the ultrasonic power of the ultrasonic immersion treatment is 400 W, and the ultrasonic time is 40 min.

[0089] The preparation method of the modified agent of this embodiment is:

[0090] Add 3 parts of carbon fiber and 4 parts of calcite powder to 7 parts of lanthanum chloride solution by weight, stir and mix, then add 4 parts of dopamine hydrochloride solution and continue to mix thoroughly to obtain a modified lanthanum solution;

[0091] The flaky nano-alumina and the modified lanthanum liquid are stirred and modified in a weight ratio of 3:5. After the stirring is completed, the mixture is filtered and dried to obtain a modified agent.

[0092] The mass fraction of the lanthanum chloride solution in this embodiment is 5%; the mass fraction of the dopamine hydrochloride solution is 4%.

[0093] The stirring speed of the stirring modification treatment in this embodiment is 750 r / min, and the stirring time is 45 min.

[0094] The specific preparation method of the coordination treatment agent of this embodiment is:

[0095] S101: immersing boron nitride in a sufficient amount of 5% by weight sodium dodecylbenzene sulfonate solution and stirring sufficiently to obtain a boron nitride liquid; then adding 5 parts of nano-silica sol and 3 parts of yttrium oxide by weight to 8 parts of the boron nitride liquid and mixing sufficiently to obtain a sol regulator;

[0096] S102: Add 4 parts of sodium carboxymethyl cellulose to 8 parts of sodium silicate solution by weight, then add 4 parts of sol regulator and stir thoroughly, then filter and dry to obtain a coordination treatment agent.

[0097] The mass fraction of the sodium silicate solution in this embodiment is 5%.

[0098] A method for preparing a diamond saw blade in this embodiment comprises the following steps:

[0099] First, diamond powder, silicon carbide, modification additives, cerium powder, nickel powder, copper powder and coordination treatment agent are mixed thoroughly, and then molded in a mold with a molding pressure of 20MPa and a molding time of 1h. After the molding is completed, demolding is performed and then sintering is performed at 850°C for 1h to obtain a diamond segment. Finally, the diamond segment and the main substrate are welded together to obtain a diamond saw blade.

[0100] Embodiment 3: A diamond saw blade, comprising a main substrate, on which a diamond bit is arranged, and the diamond bit is used for sawing a workpiece;

[0101] The diamond segment comprises the following raw materials in parts by weight:

[0102] 37.5 parts of diamond powder, 12.5 parts of silicon carbide, 11 parts of modifying additives, 3.5 parts of cerium powder, 3.5 parts of nickel powder, 3.5 parts of copper powder, and 10 parts of coordination treatment agent.

[0103] The mesh size of the diamond powder and silicon carbide in this embodiment is 800 mesh; the mesh size of the cerium powder, nickel powder and copper powder is 400 mesh.

[0104] The preparation method of the modified additive of this embodiment is:

[0105] S01: Preparation of impregnating agent:

[0106] 4 parts of mullite powder and 3 parts of zirconium silicate are mixed in 12.5 parts of potassium permanganate solution by weight, and then washed, filtered and dried to obtain composite powder;

[0107] 5 parts of composite powder, 3 parts of silane coupling agent KH550 and 2 parts of stearic acid were mixed by weight and added into 10 parts of sodium alginate solution and stirred thoroughly to obtain an impregnating agent;

[0108] S02: first immerse the kaolin in an impregnating agent of 4 times the total weight of the kaolin for ultrasonic impregnation treatment, and after the immersion is completed, a kaolin impregnation solution is obtained;

[0109] S03: The kaolin impregnation liquid and the modifying agent are mixed in a weight ratio of 3:5 and ball-milled at a speed of 1500 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water, filtered and dried to obtain the modified additive.

[0110] The mass fraction of the potassium permanganate solution in this embodiment is 3.5%; the mass fraction of the sodium alginate solution is 4%; the ultrasonic power of the ultrasonic immersion treatment is 370W, and the ultrasonic time is 35 minutes.

[0111] The preparation method of the modified agent of this embodiment is:

[0112] Add 2 parts of carbon fiber and 3 parts of calcite powder to 6 parts of lanthanum chloride solution by weight, stir and mix, then add 3 parts of dopamine hydrochloride solution and continue to mix thoroughly to obtain a modified lanthanum solution;

[0113] The flaky nano-alumina and the modified lanthanum liquid are stirred and modified in a weight ratio of 3:5. After the stirring is completed, the mixture is filtered and dried to obtain a modified agent.

[0114] The mass fraction of the lanthanum chloride solution in this embodiment is 4%; the mass fraction of the dopamine hydrochloride solution is 3%.

[0115] The stirring speed of the stirring modification treatment in this embodiment is 600 r / min, and the stirring time is 40 min.

[0116] The specific preparation method of the coordination treatment agent of this embodiment is:

[0117] S101: immersing boron nitride in a sufficient amount of 3.5% by mass sodium dodecylbenzene sulfonate solution and stirring sufficiently to obtain a boron nitride liquid; then adding 4 parts of nano-silica sol and 2 parts of yttrium oxide by weight into 6.5 parts of the boron nitride liquid and mixing sufficiently to obtain a sol regulator;

[0118] S102: Add 3 parts of sodium carboxymethyl cellulose to 6.5 parts of sodium silicate solution by weight, then add 3 parts of sol regulator and stir thoroughly, then filter and dry to obtain a coordination treatment agent.

[0119] The mass fraction of the sodium silicate solution in this embodiment is 4%.

[0120] A method for preparing a diamond saw blade in this embodiment comprises the following steps:

[0121] First, diamond powder, silicon carbide, modified additives, cerium powder, nickel powder, copper powder and coordination treatment agent are mixed thoroughly, and then molded in a mold with a molding pressure of 20MPa and a molding time of 1h. After the molding is completed, demolding is performed and then sintering is performed at 835°C for 1h to obtain a diamond segment. Finally, the diamond segment and the main substrate are welded together to obtain a diamond saw blade.

[0122] Comparative Example 1:

[0123] The difference from Example 3 is that no modifying additive is added.

[0124] Comparative Example 2:

[0125] The difference from Example 3 is that no kaolin impregnation solution is added in the preparation of the modified additive.

[0126] Comparative Example 3:

[0127] The difference from Example 3 is that no impregnating agent is used in the kaolin impregnation solution.

[0128] Comparative Example 4:

[0129] The difference from Example 3 is that no composite powder is added to the impregnating agent.

[0130] Comparative Example 5:

[0131] The difference from Example 3 is that no modifying agent treatment is used in the preparation of the modified additive.

[0132] Comparative Example 6:

[0133] The difference from Example 3 is that no coordination treatment agent is added.

[0134] Comparative Example 7:

[0135] The difference from Example 3 is that no sol regulator is added to the coordination treatment agent.

[0136] Comparative Example 8:

[0137] The difference from Example 3 is that no boron nitride liquid is added to the sol regulator.

[0138] Comparative Example 9:

[0139] The difference from Example 3 is that no nano silica sol or yttrium oxide is added to the sol regulator.

[0140] Comparative Example 10:

[0141] The difference from Example 3 is that sodium carboxymethyl cellulose is not added to the coordination treatment agent, and deionized water is used instead of the sodium silicate solution.

[0142] The products of Examples 1 to 3 and Comparative Examples 1 to 10 were subjected to conventional performance tests, and were placed under 5% humidity and 2% sodium chloride salt spray conditions for 12 hours, then placed at -5°C for 6 hours, and finally placed at 70°C for 12 hours. The above was one cycle, and the cycle was repeated 10 times. The salt spray and water resistance and cold and heat stability of the tested products were poor. The performance measurement results are shown in Table 1.

[0143] Table 1 Product performance test results of Examples 1 to 3 and Comparative Examples 1 to 10:

[0144]

[0145] It can be seen from Examples 1 to 3 and Comparative Examples 1 to 10 that the impact toughness, thermal conductivity and wear resistance of the product of Example 3 of the present invention can be improved in a coordinated manner, and the product has significant effects on salt spray and water resistance and cold and heat stability;

[0146] It can be seen from Comparative Example 1, Comparative Example 6 and Example 3 that the performance of the product is significantly deteriorated when the modifying additive and the coordinating agent are not added in the present invention. The performance effect of the product is most significant when the modifying additive and the coordinating agent are coordinated and formulated together.

[0147] It can be seen from Comparative Examples 2 to 5 and Example 3 that the performance of the products tended to deteriorate when no kaolin impregnation solution was added in the preparation of the modified additive, no impregnation agent was used in the kaolin impregnation solution, no composite powder was added to the impregnation agent, and no modification agent was used in the preparation of the modified additive. The modified additive obtained by the specific method of the present invention had the most significant product performance effect, and the performance of the product also showed a relatively obvious deterioration trend when no modification agent was used in the preparation of the modified additive.

[0148] It can be seen from Comparative Examples 7 to 10 and Example 3 that no sol regulator was added to the coordinating treatment agent, no boron nitride liquid was added to the sol regulator, no nano-silica sol and yttrium oxide were added to the sol regulator, and no sodium carboxymethyl cellulose was added to the coordinating treatment agent, and the sodium silicate solution was replaced by deionized water. The performance of the products all tended to deteriorate. The sol regulator obtained by the specific method of the present invention and the coordinating treatment agent of the specific process of the present invention had the most significant product performance effect.

[0149] Since the modification of the adjustment agent has a significant impact on the performance of the product, further research is conducted on this.

[0150] Experimental Example 1:

[0151] The only difference from Example 3 is that the modified lanthanum liquid treatment was not used in the preparation of the modified agent.

[0152] Experimental Example 2:

[0153] The only difference from Example 3 is that the flaky nano-alumina treatment is not used in the preparation of the modified agent.

[0154] Experimental Example 3:

[0155] The only difference from Example 3 is that no carbon fiber and calcite are added to the modified lanthanum solution.

[0156] Experimental Example 4:

[0157] The only difference from Example 3 is that no lanthanum chloride solution is added to the modified lanthanum solution.

[0158] Experimental Example 5:

[0159] The only difference from Example 3 is that no dopamine hydrochloride solution is added to the modified lanthanum solution.

[0160] The products of Experimental Examples 1 to 5 were subjected to conventional performance tests, and were placed under 5% humidity and 2% sodium chloride salt spray conditions for 12 hours, then placed at -5°C for 6 hours, and finally placed at 70°C for 12 hours. The above was one cycle, and the cycle was repeated 10 times. The salt spray and water resistance and cold and heat stability of the tested products were poor. The performance measurement results are shown in Table 2.

[0161] Table 2 Product performance test results of Experimental Examples 1 to 5:

[0162]

[0163] It can be seen from Experimental Examples 1-5 that the modified lanthanum liquid treatment was not used in the preparation of the modified adjuster, and the performance change trend of the product was large. At the same time, the flaky nano-alumina treatment was not used in the preparation of the modified adjuster, and carbon fiber and calcite were not added to the modified lanthanum liquid. The performance of the product showed a trend of deterioration. In addition, no lanthanum chloride solution was added to the modified lanthanum liquid, and no dopamine hydrochloride solution was added to the modified lanthanum liquid. The performance of the product showed a trend of deterioration to varying degrees. The modified adjuster obtained by improving the flaky nano-alumina with the modified lanthanum liquid obtained by combining carbon fiber, calcite and specific raw materials has the most significant product performance effect. Only the performance effect of the product prepared by using the specific raw materials of the present invention is the most significant. Other methods are not as obvious as the effect of the present invention.

[0164] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0165] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A diamond saw blade, comprising a main substrate, characterized in that: The main substrate is provided with a diamond bit, and the diamond bit is used for sawing the workpiece; The diamond segment comprises the following raw materials in parts by weight: 35-40 parts of diamond powder, 10-15 parts of silicon carbide, 9-13 parts of modifying additives, 2-5 parts of cerium powder, 2-5 parts of nickel powder, 2-5 parts of copper powder, and 8-12 parts of coordination treatment agent; The preparation method of the modified additive is: S01: Preparation of impregnating agent: 3-5 parts of mullite powder and 2-4 parts of zirconium silicate are mixed in 10-15 parts of potassium permanganate solution by weight, and then washed, filtered and dried to obtain composite powder; 4-6 parts of composite powder, 2-4 parts of silane coupling agent KH550 and 1-3 parts of stearic acid are mixed by weight and added into 8-12 parts of sodium alginate solution and stirred sufficiently to obtain an impregnating agent; S02: first immersing the kaolin in an impregnating agent of 3-5 times the total weight of the kaolin for ultrasonic impregnation treatment, and obtaining a kaolin impregnation solution after the impregnation is completed; S03: The kaolin impregnation liquid and the modified agent are mixed in a weight ratio of 3:5, and the mixture is ball-milled at a speed of 1500 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water, filtered, and dried to obtain the modified additive; The preparation method of the modified agent is: Add 1-3 parts of carbon fiber and 2-4 parts of calcite powder to 5-7 parts of lanthanum chloride solution by weight, stir and mix, then add 2-4 parts of dopamine hydrochloride solution and continue to mix thoroughly to obtain a modified lanthanum solution; The flaky nano-alumina and the modified lanthanum liquid are stirred and modified in a weight ratio of 3:5, and after the stirring is completed, the mixture is filtered and dried to obtain a modified agent; The specific preparation method of the coordination treatment agent is: S101: immersing boron nitride in a sufficient amount of 2-5% by weight sodium dodecylbenzene sulfonate solution and stirring sufficiently to obtain a boron nitride liquid; then adding 3-5 parts by weight of nano silica sol and 1-3 parts by weight of yttrium oxide to 5-8 parts of the boron nitride liquid and mixing sufficiently to obtain a sol regulator; S102: Add 2-4 parts of sodium carboxymethyl cellulose to 5-8 parts of sodium silicate solution by weight, then add 2-4 parts of sol regulator and stir thoroughly, then filter and dry to obtain a coordination treatment agent.

2. A diamond saw blade according to claim 1, characterized in that: The mesh sizes of the diamond powder and silicon carbide are both 800 meshes; the mesh sizes of the cerium powder, nickel powder and copper powder are all 400 meshes.

3. A diamond saw blade according to claim 1, characterized in that: The mass fraction of the potassium permanganate solution is 2-5%; the mass fraction of the sodium alginate solution is 3-5%.

4. A diamond saw blade according to claim 1, characterized in that: The ultrasonic power of the ultrasonic immersion treatment is 350-400W, and the ultrasonic time is 30-40min.

5. The diamond saw blade according to claim 1, characterized in that: The mass fraction of the lanthanum chloride solution is 3-5%; the mass fraction of the dopamine hydrochloride solution is 2-4%.

6. The diamond saw blade according to claim 1, characterized in that: The stirring speed of the stirring modification treatment is 550-750 r / min, and the stirring time is 35-45 min.

7. The diamond saw blade according to claim 1, characterized in that: The mass fraction of the sodium silicate solution is 3-5%.

8. A method for preparing a diamond saw blade, for preparing the diamond saw blade according to any one of claims 1 to 7, characterized in that: The following steps are involved: First, diamond powder, silicon carbide, modified additives, cerium powder, nickel powder, copper powder and coordination treatment agent are mixed thoroughly, and then molded in a mold with a molding pressure of 20MPa and a molding time of 1h. After the molding is completed, demolding is performed and then sintered at 820-850℃ for 1h to obtain a diamond segment. Finally, the diamond segment and the main substrate are welded together to obtain a diamond saw blade.

Citation Information

Patent Citations

  • Large-size seed crystal for cultivating diamonds and preparation method thereof

    CN112064120A

  • Metal sintering ultrathin cutting knife for silicon wafer cutting and preparation method

    CN114472894A